2013
DOI: 10.4161/tisb.24565
|View full text |Cite
|
Sign up to set email alerts
|

Trends in drug delivery through tissue barriers containing tight junctions

Abstract: A limitation in the uptake of many drugs is the restricted permeation through tissue barriers. There are two general ways to cross barriers formed by cell layers: by transcytosis or by diffusion through the intercellular space. In the latter, tight junctions (TJs) play the decisive role in the regulation of the barrier permeability. Thus, transient modulation of TJs is a potent strategy to improve drug delivery. There have been extensive studies on surfactant-like absorption enhancers. One of the most effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 103 publications
0
34
0
Order By: Relevance
“…Occl and Cldn ECL–derived peptides have been used to manipulate TJ structure and function at bTJs . We hypothesize that peptidomimetics of Tric ECLs specifically interfere with tTJ protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Occl and Cldn ECL–derived peptides have been used to manipulate TJ structure and function at bTJs . We hypothesize that peptidomimetics of Tric ECLs specifically interfere with tTJ protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Gene knockout and small interfering RNA (siRNA) approaches revealed that the loss of claudin‐5 expression from the BBB leads to a size‐selective permeability of the BBB for molecules with a molecular weight less than 800 Da . While, physiologically, the BBB protects the CNS against harmful blood‐borne substances, claudin‐5–mediated BBB tightening is a major obstacle for the effective delivery of hydrophilic drugs to the CNS …”
Section: Introductionmentioning
confidence: 99%
“…The promising TJ modulators Clostridium perfringens enterotoxin [46][47][48], sodium caprate [48,49] and the claudin-1 peptidomimetics [50] have also been evaluated in vivo, but do not fit entirely the definition of MB TJ modulators given above and are thus beyond the scope of this review.…”
Section: Opening Of Tjmentioning
confidence: 98%